1989
DOI: 10.1073/pnas.86.20.8098
|View full text |Cite
|
Sign up to set email alerts
|

Convergence and divergence of neurotransmitter action in human cerebral cortex.

Abstract: The postsynaptic actions of acetylcholine, adenosine, yaminobutyric acid, histamine, norepinephrine, and serotonin were analyzed in human cortical pyramidal cells maintained in vitro. The actions of these six putative neurotransmitters converged onto three distinct potassium currents.Application of acetylcholine, histamine, norepinephrine, or serotonin all increased spiking by reducing spike-frequency adaptation, in part by reducing the current that underlies the slow afterhyperpolarization. In addition, appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
183
0
6

Year Published

1991
1991
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(196 citation statements)
references
References 29 publications
7
183
0
6
Order By: Relevance
“…Beside modulating sI AHP , muscarinic and mGluR agonists induce a depolarization of the membrane potential in CA1 neurons. The underlying current has been ascribed to the inhibition of at least two types of K ϩ currents: the voltage-dependent M current (Brown and Adams, 1980;Halliwell and Adams, 1982;McCormick and Williamson, 1989) and a voltage-independent leak current (Madison et al, 1987;Guerineau et al, 1994). More recently, a cation nonselective current has been proposed to be mainly responsible for the depolarization generated by muscarinic and mGluR agonists in cortical and hippocampal neurons (Crepel et al, 1994;Greene et al, 1994;Guerineau et al, 1995;HajDahmane andAndrade, 1997, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Beside modulating sI AHP , muscarinic and mGluR agonists induce a depolarization of the membrane potential in CA1 neurons. The underlying current has been ascribed to the inhibition of at least two types of K ϩ currents: the voltage-dependent M current (Brown and Adams, 1980;Halliwell and Adams, 1982;McCormick and Williamson, 1989) and a voltage-independent leak current (Madison et al, 1987;Guerineau et al, 1994). More recently, a cation nonselective current has been proposed to be mainly responsible for the depolarization generated by muscarinic and mGluR agonists in cortical and hippocampal neurons (Crepel et al, 1994;Greene et al, 1994;Guerineau et al, 1995;HajDahmane andAndrade, 1997, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in histaminergic transmission enhances W, whereas its blockade causes somnolence (for review, see Lin, 2000). HA induces a switch in neuronal firing mode from rhythmic burst to single spike activity in thalamic relay neurons (McCormick and Williamson, 1991) and an increase in spiking by reducing spikefrequency adaptation (McCormick and Williamson, 1989). In addition, HA stimulates cholinergic neurons of the brainstem and basal forebrain (Khateb et al, 1995;Lin et al, 1996;Crochet and Sakai, 1999;Koyama and Sakai, 2000) and serotonergic neurons of the DRN (Sakai and Crochet, 2000;Brown et al, 2002), both implicated in waking and attention.…”
Section: Characteristics Of Ha Tm Neurons In Vitro and In Vivomentioning
confidence: 99%
“…Studies using intracellular current-clamp recordings have generally found mAChR activation to be excitatory, producing depolarizing responses in neurons and facilitating action potential generation (Krnjevic et al, 1971;McCormick andPrince, 1985, 1986;Schwindt et al, 1988;Halliwell, 1989;Andrade, 1991;Metherate et al, 1992;Wang and McCormick, 1993;Gloveli et al, 1999;Egorov et al, 2002Egorov et al, , 2003. These direct excitatory effects have been attributed to mAChR-mediated inhibition of potassium conductances (Krnjevic et al, 1971;Schwindt et al, 1988;McCormick and Williamson, 1989;McCormick, 1990;Nishikawa et al, 1994), although more recent data suggest that ACh may also increase activation of a nonselective cation conductance (Andrade, 1991;Andrade, 1996, 1998;Klink and Alonso, 1997;Shalinsky et al, 2002;Egorov et al, 2003).…”
Section: Introductionmentioning
confidence: 99%